Simple Economics of the US-China Trade War - Malovic, Marko G. (Poslovna ekonomija, 2019)
United States and China have recently found themselves engulfed in a full-blown trade war of epic proportions. This paper explores the probability that outcomes will match the expectations of their protagonists, weighs certain and likely costs along with potential gains for either side and discusses possible consequences for multilateral trading system as we knew it. Moreover, paper reiterates why this trade war cannot have clear winners as well as why trade wars can never serve as sustainable and meaningful substitutes for well meant trade talks. Finally, article climaxes with a warning: trade war may easily contribute to already sinister outlook of yet another global financial crisis showing up at the horizon.